GAMIFICATION EXPERIENCE AND ITS IMPACT ON ONLINE PURCHASE INTENTION ON TIKTOK SHOP - Aswar, Nurul Fadilah (Jurnal Manajemen, 2026)
Abstract: The rapid advancement of digital technology has driven significant growth in e-commerce in Indonesia, including the increasing use of gamification across various online shopping platforms. TikTok, as one of the fastest-growing platforms, has integrated gamification features to elevate user interaction and encourage purchasing behavior. This study aims to examine the influence of autonomy, rewards, and absorption on enjoyment, as well as the effect of enjoyment on online purchase intention among TikTok Shop users in Makassar City. A descriptive quantitative approach was employed, with data collected through questionnaires administered to 168 respondents aged 18–35 who shop on TikTok and engage with its gamification features. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The findings indicate that all gamification variables—autonomy, rewards, and absorption—positively and significantly influence enjoyment. Furthermore, enjoyment has a positive and significant effect on online purchase intention. These results highlight that the enjoyable experience generated by gamification features serves as a key factor in strengthening consumers’ purchase intentions on TikTok Shop. The study recommends enhancing the design of gamification elements to be more interactive and motivating in order to improve user engagement and potentially increase purchase transactions.Keywords: Gamification, Autonomy, Rewards, Absorption, Enjoyment, Online Purchace Intention, TikTok